PTSD, Depression, and Substance Use in Relation to Suicidality Risk among Traumatized Minority Lesbian, Gay, and Bisexual Youth. Issue 1 (2nd January 2016) - Smith, Brian C.; Armelie, Aaron P.; Boarts, Jessica M.; Brazil, Miquel; Delahanty, Douglas L.
Abstract : Youths who are lesbian, gay, or bisexual (LGB) are more likely than heterosexuals to commit suicide. Substance use, PTSD, and depression are independent risk factors for suicidality; however, the extent to which these factors interact to predict suicidality is unclear. The current study examined the association between substance use, PTSD symptoms (PTSS), depressive symptoms, and suicidality in a sample of 68 traumatized minority LGB youths. Participants were recruited from an LGBT community center and completed a packet of questionnaires. Substance use and depressive symptoms were positively associated with prior suicide attempts. A significant three-way interaction revealed that substance use interacted with both PTSS and depressive symptoms to increase the odds of attempted suicide. Results underscore the importance of integrating substance use components into PTSD/depression treatment to reduce suicide risk in LGB youth.